Analysis of the Effectiveness and Contribution of Restaurant Tax, Hotel Tax, and Entertainment Tax to Bekasi City's Regional Original Income in 2021-2025 - Riski Ade Junara; Twenty Mariza Syafitri (CV Edujavare Publishing, 2026)
Regional development is an obligation of the Regional Government, a form of Regional Autonomy granted by the Central Government. This study aims to determine the effectiveness and contribution of Restaurant Tax, Entertainment Tax, and Hotel Tax in the Bekasi City Government in 2021-2025. The study uses a quantitative descriptive approach. The data used are secondary data in the form of regional revenue realization reports from Badan pendapatan Daerah Kota Bekasi for 2021-2025. The analytical method used in this study is the effectiveness ratio and contribution ratio. The results show that the average Restaurant Tax is quite effective (83.3%). The average Hotel Tax is quite effective (87.7%), and the average Entertainment Tax is less effective (69.5%). In terms of contribution to Regional Original Income (PAD), Restaurant Tax results an average contribution of less (13.72%), while Hotel Tax contributes very less (1.29%), and Entertainment Tax also contributes very less (1.42%). This study concludes that Restaurant Tax, Hotel Tax, and Entertainment Tax cumulatively contribute 16.43% to PAD, so they are not yet the mainstay of PAD and there is still potential for optimization. The suggestions given are to utilize digitalization, conduct re-data collection, set realistic targets, and improve supervision